Analisis Pembiayaan Murabahah pada BMT - Mila Alfiani; Aan Zainul Anwar; Darwanto Darwanto (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2018)
Financing is one of the function of bank or microfinance institutions such as BMT, it is a facilitation of funds for the part of deficit unit. And now murabahah is the most popular transactions in the islamic financial institusions. This study was condacted on KSPPS BMT AMAN UTAMA Jepara. This study aims to analysis operationalization of murabahah financing, analysis of calculation and accountancy of murabahah, comparation the operationalization murabahah in KSPPS BMT AMAN UTAMA with Fatwa Council of Sharia National (DSN MUI), and also analysis perception of member KSPPS BMT AMAN UTAMA about murabahah financing. The method used in this study use a qualitative method using a case study approach. This study found that the operationalization of murabahah financing in KSPPS BMT AMAN UTAMA is differentiated by the process of purchasing item. There are item which bought by BMT and there are items which bought by the member (delegated). This is what makes the murabahah financing in KSPPS BMT AMAN UTAMA can not fully match with Fatwa Council of Sharia National (DSN MUI) about murabahah financing. Beside that, the other case that not match with the Fatwa Council of Sharia National (DSN MUI) are the rule about discount/cash back and also the rule about piece repayment. This study also found that the member of KSPPS BMT AMAN UTAMA still common or not understand about murabahah financing although the company have explained about murabahah financing.